Adsorption of Vanadium (V) from SCR Catalyst Leaching Solution and Application in Methyl Orange. (1st December 2016) - Sha, Xuelong; Ma, Wei; Meng, Fanqing; Wang, Ren; Fuping, Tian; Wei, Linsen
ABSTRACT: : In this study, we explored an effective and low‐cost catalyst and its adsorption capacity and catalytic capacity for Methyl Orange Fenton oxidation degradation were investigated. The catalyst was directly prepared by reuse of magnetic iron oxide (Fe3 O4 ) after saturated adsorption of vanadium (V) from waste SCR (Selective Catalytic Reduction) catalyst. The obtained catalyst was characterized by FTIR, XPS and the results showed that vanadium (V) adsorption process of Fe3 O4 nanoparticles was non‐redox reaction. The effects of pH, adsorption kinetics and equilibrium isotherms of adsorption were assessed. Adsorption of vanadium (V) ions by Fe3 O4 nanoparticles could be well described by the Sips isotherm model which controlled by the mixed surface reaction and diffusion (MSRDC) adsorption kinetic model. The results show that vanadium (V) was mainly adsorbed on external surface of the Fe3 O4 nanoparticles. The separation‐recovering tungsten (VI) and vanadium (V) from waste SCR catalyst alkaline solution through pH adjustment was also investigated in this study. The results obtained from the experiments indicated that tungsten (VI) was selectively adsorbed from vanadium (V)/tungsten (VI) mixed solution in certain acidic condition by Fe3 O4 nanoparticle to realize their recovery. Tungsten (V) with some impurity can be obtained by releasing from adsorbent, which can be confirmed by ICP‐AES. The Methyl Orange degradation catalytic performance illustrated that the catalyst could improve Fenton reaction effectively at pH = 3.0 compare to Fe3 O4 nanoparticles alone. Therefore, Fe3 O4 nanoparticle adsorbed vanadium (V) has a potential to be employed as a heterogeneous Fenton‐like catalyst in the present contribution, and its catalytic activity was mainly evaluated in terms of the decoloration efficiency of Methyl Orange.